Systematic Review and Descriptive Synthesis of Behaviour Change Techniques in Physical Activity Interventions During and Beyond Breast Cancer - Alejandro Dominguez Garcia; Barbara A. Mullan; Kylie Hill; Lauren J. Breen; Chloe Maxwell‐Smith (Lifestyle Medicine, 2026)
ABSTRACT Purpose Many interventions aim to support women with and after a breast cancer diagnosis to increase physical activity; however, the behaviour change components supporting long‐term effectiveness remain unclear. This review examined the behaviour change techniques used in physical activity interventions in breast cancer populations that reported long‐term behavioural outcomes (≥12 weeks post‐intervention). Methods Six databases (CINAHL Ultimate, Medline, ProQuest, PsycINFO, Scopus, Web of Science) were searched in September 2024 and January 2026 for physical activity interventions for women with and beyond breast cancer that included behavioural measures ≥12 weeks after intervention completion. Behaviour change techniques were coded using the Behaviour Change Technique Taxonomy, and effect size estimates for long‐term physical activity outcomes were calculated in R and synthesised descriptively. Risk of bias was assessed using the Joanna Briggs Institute critical appraisal tools. Results Thirty‐eight studies (53 intervention groups; 4661 participants) were included. Interventions included between 2 and 18 behaviour change techniques; however, reporting often lacked sufficient operational detail to determine how techniques were implemented. Several techniques appeared inconsistently applied or misaligned with their intended mechanisms of action. Although most interventions cited behavioural theory, links between theoretical constructs and intervention content were often unclear. No meaningful patterns were identified between individual techniques and long‐term physical activity outcomes. Risk of bias was high, with common issues related to blinding and reporting. Conclusion Improved reporting, operationalisation and theoretical grounding of behaviour change interventions is needed to increase transparency and inform future interventions to promote quality of life through physical activity after treatment.